Spatial Analysis of the Distribution of COVID-19 Vulnerable Groups to COVID-19 Cases in Brebes Regency - Fatimatuzzahro, Fatimatuzzahro; Gayatri, Rara Warih (Preventia: The Indonesian Journal of Public Health, 2023)
The number of COVID-19 cases in Brebes Regency within a year is still quite high. The elderly, Hypertension and Diabetes Mellitus are the most important COVID-19 vulnerable groups and have the highest risk of death. The purpose of this study is to determine the distribution of COVID-19 vulnerable groups and their spatial relationship to COVID-19 cases in Brebes Regency. This study used a correlation or ecology study design. The data used is secondary data obtained from the Brebes Regency Health Office, namely the number of COVID-19 cases, the number of elderly, people with hypertension and diabetes mellitus in 2021. The data then analyzed using univariate, bivariate analysis and spatial analysis with the help of QuantumGIS software (QGIS). The results showed that the proportion of the elderly age group correlated with the number of COVID-19 cases (p value is 0.005), while the prevalence of hypertension and diabetes mellitus had no correlation with the number of COVID-19 cases (p value more than 0.05). The high-risk areas are Brebes, Wanasari, Banjarharjo and Bumiayu Districts. The existence of this study, the local government is expected to be able to optimize the Testing, Tracing and Treatment program (3T), posyandu for the elderly and achieve vaccination targets, especially in high elderly population areas, in order to detect and predict the spread of COVID-19 and the selection of appropriate treatment.